Análise de fácies e reconstituição paleoambiental do limite entre as Formações Cabeças e Longá da bacia do Parnaíba região de Juazeiro do Piauí - MORASCHE, Raoni Dias (2019)
The Late Devonianian-Early Carboniferous interval of the Parnaíba Basin represented by Cabeças and Longá formations records important changes in paleoenvironmental conditions of the basin. The migration of Gondwana paleocontinent since Polar Regions to subtropical areas caused relative impact in the sedimentation of the basin. Outcrop-based facies and straigraphic analisys of Cabeças and Longá formations, in Juazeiro do Piauí (PI), northeastern edge of the basin, allowed identify how the sedimentation conditions were influenced by climate changes generating different architectures of depositional system. The facies analysis permitted the individualization of 11 sedimentary facies: shale (Fl), massive siltstone (Fm), massive sandstone (Sm), parallel laminated sandstone (Sh), ripple laminated sandstone (Sr), cross laminated sandstone (St), climbing ripples cross laminated sandstone (Scr), hummocky cross bedding sandstone (Sl), swaley cross bedding sandstone (Sls), convolute bedding sandstone (Sc) and sigmoidal cross bedding sandstone (Ss). The sedimentary facies were grouped in three facies associations (FA) that registers the implementation of a deltaic front dominated by fluvial processes (AF1) of Cabeças Formation which was drowned by rising sea level, followed by an implantation of a coastal platform dominated by good weather waves and storm (AF2 and AF3) of Longá Formation. The AF3, in particular, registers tabular layers characterized by cyclical intercalation between sandstone facies and shale here interpreted as turbidity deposit. The presence of sedimentary facies associated to turbidites in Longá Formation is described in an unprecedented way in this research and may represent a porous interval in the main sealant unit on the Mesodevoniano-Eocarbonífero oil system of Parnaíba Basin. This finding promotes the need to carry out new petrophysical studies in these layers in order to confirm the potential of these rocks as a possible secondary reservoir.